Os salões e sistema da arte - os salões da Caixego nos anos 1970 - Coelho, Aguinaldo Caiado de Castro Aquino (2015)
This research aims to analyse and reflect on the Competitive Art Fair Event, System of the Art and the editions of the Annual Visual Art Contests that were held in the 1970’s decade by the bank Caixa Econômica do Estado de Goiás – that became known by Caixego Competitives Art Fairs. Five editions were held. The first one in regional or state terms, conceived in January and launched in July, 1973 , and the other four ones had a national character, from 1974 to 1977. The artistic collection resulting from the awarded works was the main former of the Contemporaneous Art Museum of Goiás, situated in Goiânia. A bibliographic and documental research was done in Caixego and museums files, local newspapers, microfilm images and open interviews with managers, organizers and artists who participated in the aforementioned Art Fairs and also professionals who work in current Art Fairs. The analysis of the characteristics of Caixego Competitives Art Fairs in comparison to the National Art Fairs, from that time and present ones, together with the concepts and evolution of the Competitive Art Fair Event and of the System of the Art, in national terms, but mainly in the State of Goiás in the 1970’s decade, with their elements and actors, constitute the objectives of this thesis. It also intends to investigate the Competitive Art Fairs capacity to gather collections for the Public Museums and the way in which they configure a strategic action of public Policy for identity construction and cultural projection of the State. The original purpose of Caixego Competitives Art fairs , as explained by the directors of the bank and by the then State Governor, was to form an art work Collection made by artists not only from Goiás but also national ones, some already well-known and others still new , and to promote nationally the Art made in Goiás. The Caixego Competitives Art Fairs had an effective participation of the artists from Goiás and also from a number of Brazilian States, nationwide wellknown invited artists, selected by active critics, who were jurors of São Paulo Bienal ( Biennial) and of the major National Competitives Art Fairs.